Emergent Percutaneous Nephrostomy for Pyonephrosis: A Primer for the On-Call Interventional Radiologist - Florido, Christopher; Herren, Josi L.; Pandhi, Mithil B.; Niemeyer, Matthew M. (Seminars in Interventional Radiology, 2020)
Pyonephrosis is gross accumulation of pus within an obstructed renal collecting system that, if left untreated, can lead to potentially fatal septic shock. Treatment requires urgent decompression coupled with systemic antibiotics. Percutaneous nephrostomy (PCN) placement, first described in 1976 for the treatment of pyonephrosis, is now widely utilized for emergent decompression in these patients. When performed by an experienced interventional radiologist, PCN is a safe procedure with technical success rates of over 96 to 99%. This article will address the clinical presentation of pyonephrosis, and will discuss the indications, technique, complications, and outcomes of emergent PCN placement. Additionally, the expanded indications for PCN placement in nonemergent scenarios will also be described.
Keywords: pyonephrosis; nephrostomy; hydronephrosis; nephrolithiasis; interventional radiology